The roles of testicular nuclear receptor 4 (TR4) in male fertility-priapism and sexual behavior defects in TR4 knockout mice - Bao Bo-Ying; Uno Hideo; Meshul Charles K; Liu Ning-Chun; Lin Wen-Jye; Ting Huei-Ju; Lee Yi-Fen; Collins Loretta L; Chen Yen-Ta; Chang Chawnshang (BMC, 2011)
Abstract Background Successful reproductive efforts require the establishment of a situation favorable for reproduction that requires integration of both behavior and internal physiological events. TR4 nuclear receptor is known to be involved in male fertility via controlling spermatogenesis, yet its roles in regulating other biological events related to reproduction have not been completely revealed. Methods Male TR4 knockout (TR4-/-) and wild type mice were used for the sexual behavior and penile dysfunction studies. Mice were sacrificed for histological examination and corresponding genes profiles were analyzed by quantitative RT-PCR. Reporter gene assays were performed. Results We describe an unexpected finding of priapism in TR4-/- mice. As a transcriptional factor, we demonstrated that TR4 transcriptionally modulates a key enzyme regulating penis erection and neuronal nitric oxide synthese NOS (nNOS). Thereby, elimination of TR4 results in nNOS reduction in both mRNA and protein levels, consequently may lead to erectile dysfunction. In addition, male TR4-/- mice display defects in sexual and social behavior, with increased fear or anxiety, as well as reduced mounting, intromission, and ejaculation. Reduction of ER alpha, ER beta, and oxytocin in the hypothalamus may contribute to defects in sexual behavior and stress response. Conclusions Together, these results provide in vivo evidence of important TR4 roles in penile physiology, as well as in male sexual behavior. In conjunction with previous finding, TR4 represents a key factor that controls male fertility via regulating behavior and internal physiological events.